Hunger modulates perceptions of food health but not taste in restricted eaters - Herrero, Lucia; McCrea, Cindy E. (Frontiers in Psychology, 2023)
Food taste and health perceptions are of particular interest for their implications on food choice. Most in vivo food choice studies experimentally control for hunger via a set preload or fast. To explore how hunger may interact with these perceptions to impact food decisions, we compared taste and health perceptions of sweet and savory obesogenic food items among hungry or satiated participants with varying restrained eating tendencies. In our sample of 232 adults (M BMI = 25.9; M age = 36.4 yrs), highly palatable foods were perceived as tasty but unhealthy. Tastiness ratings were high, consistent across restrained eating groups, and unassociated with hunger. Perceptions of health, however, were impacted by the interaction of restrained eating group and hunger. Amongst hungry participants only, a graded association between restrained eating group and perceptions of health emerged for both food types. Specifically, hungry and highly restrained eaters viewed sweet foods as 2.8x healthier and savory foods as 2.1x healthier than their satiated counterparts. Our data suggest that hunger predicts differential health perceptions, but not tastiness ratings, among restrained eaters. We argue that the generalization of food perception data-especially among different eater types-may be limited if the continuum of hunger level is experimentally constrained. Therefore, hunger is a critical dynamic to consider in explorations of food perceptions and eating behavior in restrained eaters.